Prenatal and childhood exposure to air pollution and traffic and the risk of liver injury in European children. Issue 3 (11th June 2021) - Garcia, Erika; Stratakis, Nikos; Valvi, Damaskini; Maitre, Léa; Varo, Nerea; Aasvang, Gunn Marit; Andrusaityte, Sandra; Basagana, Xavier; Casas, Maribel; de Castro, Montserrat; Fossati, Serena; Grazuleviciene, Regina; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Nonalcoholic fatty liver disease is the most prevalent pediatric chronic liver disease. Experimental studies suggest effects of air pollution and traffic exposure on liver injury. We present the first large-scale human study to evaluate associations of prenatal and childhood air pollution and traffic exposure with liver injury. Methods: Study population included 1, 102 children from the Human Early Life Exposome project. Established liver injury biomarkers, including alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transferase, and cytokeratin-18, were measured in serum between ages 6–10 years. Air pollutant exposures included nitrogen dioxide, particulate matter <10 μm (PM10 ), and <2.5 μm. Traffic measures included traffic density on nearest road, traffic load in 100-m buffer, and inverse distance to nearest road. Exposure assignments were made to residential address during pregnancy (prenatal) and residential and school addresses in year preceding follow-up (childhood). Childhood indoor air pollutant exposures were also examined. Generalized additive models were fitted adjusting for confounders. Interactions by sex and overweight/obese status were examined. Results: Prenatal and childhood exposures to air pollution and traffic were not associated with child liver injury biomarkers. There was a significant interaction between prenatal ambient PM10 and overweight/obese status for alanine aminotransferase, with stronger associations among children who were overweight/obese. There was no evidence of interaction with sex. Conclusion: This study found no evidence for associations between prenatal or childhood air pollution or traffic exposure with liver injury biomarkers in children. Findings suggest PM10 associations maybe higher in children who are overweight/obese, consistent with the multiple-hits hypothesis for nonalcoholic fatty liver disease pathogenesis.